Abundant and rare subcommunity assemblages of prokaryotes and eukaryotes controlled by vertical environmental heterogeneity in an urban reservoir - Xun Wang; Huai-yu Cao; Jia-wen Gan; Tang Liu; Pei-fang Wang; Qiu-sheng Yuan; Xiao-lei Xing; Cheng-gong Du; Yu-ran Zheng; Yun-xin Liu (Water Science and Engineering)
Reservoirs play a critical role in addressing water resources challenges. However, their vertical influence on the assembly mechanisms of different microbial communities, including prokaryotes and eukaryotes, remains unclear. This study examined the vertical diversity patterns of abundant and rare subcommunities of prokaryotes and eukaryotes in an urban reservoir, using water depth as a geographical gradient and employing high-throughput sequencing. The impact of vertical environmental heterogeneity on community structure was quantified, and key drivers of these dynamics were identified. The results indicated that the urban reservoir exhibited statistically significant differences in the vertical distribution of water temperature and oxidation/reduction potential. The α-diversity of the abundant subcommunity displayed an opposing vertical pattern compared to that of the rare subcommunity, while the β-diversity for both subcommunities of prokaryotes and eukaryotes increased with water depth. Moreover, the distinct diversity patterns of abundant and rare subcommunities were associated with environmental heterogeneity and species adaptability. Notably, the β-diversity of the rare subcommunity of eukaryotes was primarily driven by species turnover in surface water, whereas nestedness became the dominant factor in deeper water. Furthermore, eukaryotic microbes exhibited a more pronounced response to changes in water depth than prokaryotes, consistent with the importance of heterogeneous selection to the eukaryotic community. Water temperature significantly affected the community composition of all groups, highlighting its importance in shaping community dynamics. This study provides valuable insights into the vertical distribution and assembly mechanisms of microbial communities in urban reservoirs, contributing to the protection and management of aquatic ecosystems under river regulation.